The Polycomb group protein EED is dispensable for the initiation of random X-chromosome inactivation. - Sundeep Kalantry; Terry Magnuson (PLoS Genetics)
The Polycomb group (PcG) proteins are thought to silence gene expression by modifying chromatin. The Polycomb repressive complex 2 (PRC2) plays an essential role in mammalian X-chromosome inactivation (XCI), a model system to investigate heritable gene silencing. In the mouse, two different forms of XCI occur. In the preimplantation embryo, all cells undergo imprinted inactivation of the paternal X-chromosome (Xp). During the peri-implantation period, cells destined to give rise to the embryo proper erase the imprint and randomly inactivate either the maternal X-chromosome or the Xp; extraembryonic cells, on the other hand, maintain imprinted XCI of the Xp. PRC2 proteins are enriched on the inactive-X during early stages of both imprinted and random XCI. It is therefore thought that PRC2 contributes to the initiation of XCI. Mouse embryos lacking the essential PRC2 component EED harbor defects in the maintenance of imprinted XCI in differentiating trophoblast cells. Assessment of PRC2 requirement in the initiation of XCI, however, has been hindered by the presence of maternally derived proteins in the early embryo. Here we show that Eed-/- embryos initiate and maintain random XCI despite lacking any functional EED protein prior to the initiation of random XCI. Thus, despite being enriched on the inactive X-chromosome, PcGs appear to be dispensable for the initiation and maintenance of random XCI. These results highlight the lineage- and differentiation state-specific requirements for PcGs in XCI and argue against PcG function in the formation of the facultative heterochromatin of the inactive X-chromosome.